Calcretes of the Bauru Group ( Cretaceous), Brazil; petrology and geological significance. - Suguio, K.; Barcelos, J. H. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 1983)
Reinterprets petrologic studies and their geologic significance in the light of recent literature on the calcretes in the world, and the recent revision of Bauru Group stratigraphy.-from English summary